Bates Motel - Farmiga, Vera 1973-; Highmore, Freddie 1992-; Thieriot, Max 1988-
A modern day re-imagining of, and prequel to, the classic film Psycho. The story follows Norman Bates' teenage years, delving into his intricate relationship with his mother, and how she helped forge the most infamous serial killer of them all
Orig.: USA, TV-Serie, 2013 - 2017
Keywords: Serial murderers -- Drama.; Mothers and sons -- Drama.; Crime films; Television series; Sohn; Fernsehserie; Horrorfilm; Mutter; Mystery -- Film; Mordserie; Rückfalltäter; Kriminalserie; Film; DVD-Video